Respuesta :
Answer:
We conclude that the statement For positive values of x, g(x) > h(x) is TRUE.
Step-by-step explanation:
Considering the functions
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]h\left(x\right)\:=\:-x[/tex]
Checking the statement: For any value of x, g(x) will always be greater than h(x)
As
- [tex]g\left(x\right)\:=\:x^2[/tex] represents the square of an independent variable x.
- [tex]h\left(x\right)\:=\:-x[/tex] represents the negative of an independent variable x.
For example,
Putting x = 1 in [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex]
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]g\left(1\right)\:=\:\left(1\right)^2[/tex]
[tex]g\left(1\right)\:=\:1[/tex]
Also
[tex]h\left(x\right)\:=\:-x[/tex]
[tex]h\left(1\right)\:=\:-1[/tex]
But, if we put x = 0, both [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex] becomes zero.
And if we put x = -1, then again the values of both [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex] will be same which is 1.
Therefore, it is NOT TRUE that For any value of x, g(x) will always be greater than h(x).
Checking the statement: h(x) will always be greater than g(x)
This statement is false.
For example,
Putting x = 1 in [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex]
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]g\left(1\right)\:=\:\left(1\right)^2[/tex]
[tex]g\left(1\right)\:=\:1[/tex]
Also
[tex]h\left(x\right)\:=\:-x[/tex]
[tex]h\left(1\right)\:=\:-1[/tex]
So, putting x = 1 would bring [tex]g\left(x\right)\:=\:x^2[/tex] being greater than [tex]h\left(x\right)\:=\:-x[/tex].
Therefore, it is NOT TRUE that For any value of x, h(x) will always be greater than g(x).
Checking the statement: g(x) > h(x) for x = -1
Considering
- [tex]g\left(x\right)\:=\:x^2[/tex]
- [tex]h\left(x\right)\:=\:-x[/tex]
Putting x = -1 in [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex]
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]g\left(-1\right)\:=\:\left(-1\right)^2[/tex]
[tex]g\left(-1\right)\:=\:1[/tex]
Also
[tex]h\left(x\right)\:=\:-x[/tex]
[tex]h\left(-1\right)\:=\:-\left(-1\right)[/tex]
[tex]h\left(-1\right)\:=\:1[/tex]
So, when we put x = -1, [tex]g\left(x\right)=h\left(x\right)[/tex]
i.e. [tex]g\left(-1\right)=h\left(-1\right)[/tex]
Therefore, it is NOT TRUE that g(x) > h(x) for x = -1.
Checking the statement: For positive values of x, g(x) > h(x)
Since
- [tex]g\left(x\right)\:=\:x^2[/tex] represents the square of an independent variable x.
- [tex]h\left(x\right)\:=\:-x[/tex] represents the negative of an independent variable x.
So, for positive values of x, g(x) > h(x)
For example,
Putting x = 1 in [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex]
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]g\left(1\right)\:=\:\left(1\right)^2[/tex]
[tex]g\left(1\right)\:=\:1[/tex]
Also
[tex]h\left(x\right)\:=\:-x[/tex]
[tex]h\left(1\right)\:=\:-1[/tex]
Therefore, the statement For positive values of x, g(x) > h(x) is TRUE.
Checking the statement: For negative values of x, g(x) > h(x)
Considering
- [tex]g\left(x\right)\:=\:x^2[/tex]
- [tex]h\left(x\right)\:=\:-x[/tex]
Putting x = -1 in [tex]g\left(x\right)\:=\:x^2[/tex] and [tex]h\left(x\right)\:=\:-x[/tex]
[tex]g\left(x\right)\:=\:x^2[/tex]
[tex]g\left(-1\right)\:=\:\left(-1\right)^2[/tex]
[tex]g\left(-1\right)\:=\:1[/tex]
Also
[tex]h\left(x\right)\:=\:-x[/tex]
[tex]h\left(-1\right)\:=\:-\left(-1\right)[/tex]
[tex]h\left(-1\right)\:=\:1[/tex]
So, when we put x = -1, [tex]g\left(x\right)=h\left(x\right)[/tex]
Therefore, the statement For negative values of x, g(x) > h(x) is NOT TRUE.
Therefore, from the entire discussion above, we conclude that the statement For positive values of x, g(x) > h(x) is TRUE.
Keywords: function, composition function
Learn more about composition of function from brainly.com/question/12293021
#learnwithBrainly